Observation on the Evaluation of Machine Learning Algorithms Across Diverse Application Domains (Al-Farooq Journal of Sciences, 2026)
The rapid integration of machine learning (ML) across scientific, industrial, and commercial sectors has outpaced the development of standardized evaluation protocols. This observational study critically examines how ML algorithms are evaluated across five high-impact domains: healthcare, finance, industrial engineering, agriculture/environmental monitoring, and autonomous systems. By synthesizing peer-reviewed literature published between 2018 and 2025, we identify recurring methodological patterns, metric misalignments, validation shortcomings, and domain-specific evaluation constraints. Our analysis reveals that while technical performance metrics dominate algorithmic benchmarking, operational relevance, temporal/spatial data structures, and risk-aware validation are frequently underrepresented. We further observe a systemic disconnect between laboratory-stage evaluation and deployment-phase monitoring, contributing to reproducibility gaps and inconsistent real-world utility. To address these limitations, we propose a domain-aware evaluation framework that aligns metric selection with operational consequences, enforces structurally appropriate validation strategies, and mandates uncertainty and robustness reporting. The findings underscore the necessity of context-sensitive evaluation paradigms and interdisciplinary collaboration in ML assessment practices.
Keywords: Machine learning evaluation, domain adaptation, performance metrics, algorithmic benchmarking, validation strategies, reproducibility in AI, cross-disciplinary machine learning